Penerapan Knowledge Managemen System Life Cycle (KMSLC) Pada Pelayanan Manajeman Kantin - Prayitna, Graciella; Jose, Abednego; Nurwegiono, Muhammad; Parga Zen, Bita (Jurnal Sistem Informasi Galuh, 2025)
Dee Canteen at Ma Chung University faces challenges in knowledge management related to operations, including a lack of documentation for tacit and explicit knowledge such as quick cooking techniques and kitchen SOPs. This study aims to develop a Knowledge Management System (KMS) using the Knowledge Management System Life Cycle (KMSLC). The research methodology includes collecting tacit knowledge through expert interviews, converting the knowledge into explicit forms, and designing a system based on a Knowledge Map. The results of the study show that the implementation of KMS can enhance knowledge documentation and transfer, support operational standardization, and improve the quality of canteen services. The designed system includes key features such as recipe documentation, SOPs, and customer feedback, which can be efficiently accessed by the team.